Faktor yang Menyebabkan Kredit Macet pada Debitur di Bank BRI Unit Pasar Baru Balikpapan - Afifah Zakiati; Ovigeria Subroto Sinaga (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
Indonesian population growth has influenced the growth of the economy. Banks are needed to support economic activity. To boost economic growth, the banking sector plays an important role in the economy in raising funds and re-routing them. The purpose of the research is to find the credit factor blocked by the bank in the distribution of funds carried out. Analysed using qualitative descriptive methods, the factors causing credit crashes are so diverse and include complex internal and external factors that require good risk management, careful assessment of debtors, as well as an in-depth understanding of the economic and legal conditions applicable in reducing the risk of credit crises.